The relationship between Dietary approaches to stop hypertension diet adherence and inflammatory factors and insulin resistance in overweight and obese women: A cross-sectional study. (December 2021) - Taheri, Akram; Mirzababaei, Atieh; Setayesh, Leila; Yarizadeh, Habib; Shiraseb, Farideh; Imani, Hossein; C.T. Clark, Cain; Mirzaei, Khadijeh
Abstract: Background: Although there is abundant evidence for an association between dietary pattern, weight, and other related factors, such as homeostatic model assessment for insulin resistance (HOMA-IR) and inflammatory markers; there is limited information pertaining to levels of plasminogen activator inhibitor-1 (PAI-1) and Monocyte Chemoattractant Protein −1 (MCP-1). Therefore, this study sought to examine the association between adherence to the dietary approaches to stop hypertension (DASH) diet and levels of inflammatory factors PAI-1, MCP-1, and HOMA-IR. Methods: This cross-sectional study was performed on 305 obese and overweight women. The typical food intake of individuals was assessed using the 147 items semi-quantitative food frequency questionnaire (FFQ). Body components were measured for all participants. Insulin resistance was estimated by homeostasis model assessment (HOMA), and biochemical parameters were examined. Results: No significant relationship was observed between the DASH diet and MCP-1 (P-trend = 0.70), PAI-1 (P-trend = 0.92), or HOMA-IR (P-trend = 0.08) in the crude model. However, there was a significant inverse relationship between the DASH diet and HOMA-IR (P-trend = 0.03) after adjusting for age, BMI, and physical activity. Conclusion: This study showed that higher adherence to DASH pattern is inversely correlated with HOMA-IR in overweight and obese women.